Residências Universitárias: Uma Revisão da Literatura /University Residences: A Literature Review - Tavares, Fernando Oliveira; Pacheco, Luís Dias; Pereira, Elisabeth Teixeira (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2018)
O objetivo deste artigo é fazer uma revisão da literatura sobre o tema das residências universitárias e perceber em nível da literatura internacional sobre o assunto, quais as variáveis e fatores que são importantes para o estudante. No início do artigo são compilados os estudos relacionados com a qualidade de vida e ambiente de uma residência universitária e, seguidamente, são apresentados estudos sobre as externalidades positivas (amenidades) destas residências. Posteriormente, são referidos estudos sobre as preferências dos estudantes relacionadas com o espaço físico e acomodação das residências. Finalmente, são apresentados estudos sobre os fatores físicos da construção que influenciam as residências e acerca das atitudes ambientais por parte dos estudantes. Claramente, constata-se que existem elementos de qualidade, de ambiente, de espaço físico e de acomodação que estão relacionados com a satisfação dos estudantes nas residências universitárias. PALAVRAS-CHAVE Residência Universitária. Revisão de Literatura. Qualidade de Vida. Espaço Físico. Atitudes Ambientais. ABSTRACT The purpose of this article is to review the literature on the subject of university residences and to understand international literature on the subject, what variables and factors are important to the student. The paper begins by compiling studies related to the quality of life and environment of a university residence and, next, studies concerning the positive externalities (amenities) of those residences are presented. Subsequently, studies are reported on the preferences of students related to the physical space and accommodation of the residences. Finally, studies are presented on the physical factors of the construction that influence the residences and environmental attitudes of its students. Clearly, elements of quality, environment, physical space and accommodation are related to the students’ satisfaction in university residences. KEYWORDS University Residences. Literature Review. Quality of Life. Space. Environmental Attitudes. AUTORES Fernando Oliveira Tavares – Doutor. Professor na Universidade Portucalense Infante D. Henrique, Porto, Portugal. Currículo: http://orcid.org/0000-0002-9672-8770. E-mail: ftavares@upt.pt Luís Dias Pacheco – Doutor. Professor na Universidade Portucalense Infante D. Henrique, Porto, Portugal. Currículo: http://orcid.org/0000-0002-9066-6441. E-mail: luisp@upt.pt Elisabeth Teixeira Pereira – Doutora. Professora na Universidade de Aveiro - Campus Universitário de Santiago, Aveiro, Portugal. Currículo: http://orcid.org/0000-0001-8997-1249. E-mail: melisa@ua.pt REFERENCIAS AlKandari, N. (2007). Students' perceptions of the residence hall living environment at Kuwait University. College Student Journal, 41(2), 327-335. Línk Amole, D. (2005). Coping strategies for living in student residential facilities in Nigeria. Environment and Behavior, 37(2), 201-219. Link Amole, D. (2009). Residential satisfaction in students’ housing. Journal of Environmental Psychology, 29(1), 76-85. Link Ballou, R., Reavill, L. & Schultz, B. (1995). Assessing the immediate and residual effects of the residence hall experience: Validating Pace's 1990 study of on-campus and off campus students. Journal of College and University Student Housing, 25, 16-21. Link Balogh, C. P., Grimm, J. & Hardy, K. (2005). ACUHO-I Construction and renovation data: the latest trends in housing construction and renovation. Journal of College and University Student Housing, 33(2), 82-91. <a href="http://search.ebscohost.com/login.aspx?direct=true&profile=ehost&scope=site&authtype=crawler&jrnl=0161827X&AN=59756851&h=umzyZyYHGfpiLcqw62a9HvIbCZJeIOEvKZHgqKX1fu8uWTdWDWDx3GYwtVq38mi1G3%2FTvrvGMzRvdmeM2HZObQ%3D%3D&crl=c">Link Bekurs, G. (2007). Outstanding student housing in American community colleges: problems and prospects. Community College Journal of Research and Practice, 31(8), 621-636. Link Berlatto, F. & Sallas, A. L. F. (2008). Um lar em terra estranha: espaço e sociabilidade em uma casa de estudantes feminina. Revista Chilena de Antropologia Visual, 12, 48-69. Link Butler, D. L. & Biner, P. M. (1989). Effects of setting on window preferences and factors associated with those preferences. Environment and Behavior, 21(1), 17-31. Link Butler , D. L. & Steuerwald, B. L. (1991). In models effects of view and room size on window size preferences made in models. Environment and Behavior, 23(3), 334-358. Link Cross, J. E., Zimmerman, D. & O’Grady, M. A. (2009). Residence hall room type and alcohol use among college students living on campus. Environment and Behavior, 41(4), 583-603. Link Delabrida, Z. N. C. (2014). Variáveis individuais, sociais e do ambiente físico em residências universitárias. Psico, 45(3), 10-20. Link Devlin, A. S. (1994). Gender-role and housing preferences. Journal of Environmental Psychology, 14(3), 225-235. Link Devlin, A. S., Donovan, S., Nicolov, A., Nold, O. & Zandan, G. (2008). Residence hall architecture and sense of community everything old is new again. Environment and Behavior, 40(4), 487-521. Link Dusselier, L., Dunn, B., Wang, Y., Shelley, M. C. & Whalen, D. F. (2005). Personal, health, academic, and environmental predictors of stress for residence hall students. Journal of American College Health, 54(1), 15-24. Link Ferraz, N. O. (2011). Desenvolvimento pessoal e social e a influência da envolvente física. (Mestrado), Universidade de Aveiro, Aveiro - Portugal. Link Fior, C. A., Mercuri, E. & Almeida, L. D. S. (2011). Escala de interação com pares: construção e evidências de validade para estudantes do ensino superior. Psico-USF, 16(1), 11-21. Link Galambos, N. L., Howard, A. L. & Maggs, J. L. (2011). Rise and fall of sleep quantity and quality with student experiences across the first year of university. Journal of Research on Adolescence, 21(2), 342-349. Link Garrido, E. N. (2015). Experience of living in a college residence hall: Impact on its residents. Psicologia: Ciência e Profissão, 35(3), 726-739. Link Garrido, E. N. & Mercuri, E. (2013). A moradia estudantil universitária como tema na produção científica nacional. (Revista Semestral da Associação Brasileira de) Psicologia Escolar e Educacional, 17(1), 87-95. Link Gifford, R. (2014). Environmental psychology matters. Annual Review of Psychology, 65, 541-579. Link Hassanain, M. A. (2008). On the performance evaluation of sustainable student housing facilities. Journal of Facilities Management, 6(3), 212-225. Link Holahan, C. J. & Wilcox, B. L. (1978). Residential satisfaction and friendship formation in high and low rise student housing: an interactional analysis. Journal of Educational Psychology, 70(2), 237-241.Link Iftikhar, A. & Ajmal, A. (2015). A qualitative study investigating the impact of hostel life. International Journal of Emergency Mental Health and Human Resilience, 17(2), 511-515. Link Jabareen, Y. (2005). Culture and housing preferences in a developing city. Environment and Behavior, 37(1), 134-146. Link Jacobs, J. & Archie, T. (2008). Investigating sense of community in first-year college students. The Journal of Experiential Education, 30(3), 282-285. Link Kagawa, F. (2007). Dissonance in students' perceptions of sustainable development and sustainability: Implications for curriculum change. International Journal of Sustainability in Higher Education, 8(3), 317-338. Link Karlin, R. A., Rosen, L. S. & Epstein, Y. M. (1979). Three into two doesn't go: A follow-up on the effects of overcrowded dormitory rooms. Personality and Social Psychology Bulletin, 5(3), 391-395. Link Kaya, N. & Erkip, F. (2001). Satisfaction in a dormitory building: The effects of floor on the perception of room size and crowding. Environment and Behavior, 33(1), 35-53. Link Khozaei, F., Ayub, N., Hassan, A. S. & Khozaei, Z. (2010). The factors predicting students' satisfaction with university hostels: case study University Sains Malaysia. Asian Culture and History, 2(2), 148-158. Link Khozaei, F., Hassan, A. S. & Ramayah, T. (2011a). The students’ degree of preference for residence hall facilities and amenities, study of a developing country. African Journal of Business Management, 5(17), 7335-7341. Link Khozaei, F., Hassan, A. S. & Ramayah, T. (2011b). Development and validation of the student accommodation preferences instrument [SAPI]. Journal of Building Appraisal, 6(3-4), 299-313. Link Khozaei, F., Ramayah, T. & Hassan, A. S. (2012). A shorter version of Student Accommodation Preferences Index [SAPI]. American Transactions on Engineering & Applied Sciences, 1(3), 195-211. <a href="https://www.researchgate.net/profile/Fatemeh_Khozaei/publication/303405632_A_Shorter_Version_of_Student_Accommodation_Preferences_Index_SAPI/links/5741c7f808aea45ee84a32f1/A-Shorter-Version-of-Student-Accommodation-Preferences-Index-SAPI.pdf">Link Koester, R., Eflin, J. & Vann, J. (2006). Beyond Disciplines: Integrating Academia, Operations, and Community for Campus wide Education for Sustainability. Inside and Out: Universities and Education for Sustainable Development. Amityville, NY: Baywood Publishing, 41-64. Laranjo, T. H. M. & Soares, C. B. (2006). Moradia universitária: processos de socialização e consumo de drogas. Revista de Saúde Pública, 40(6), 1027-1034. Link Lawless, J. W. (2012). Moving home to college: socio-physical factors in creating ‘home’ in temporary environments. Doctor of Philosophy, University of Kansas, Lawrence. Link Milman, A., Jones, F. & Bach, S. (1999). The impact of security devices on tourists’ perceived safety: The central Florida example. Journal of Hospitality and Tourism Research, 23(4), 371-386. Link Mimrot, B. H. (2012). A comparative study on the effect of the residence area on the emotional intelligence of the std. 10th female students staying in the hostel and in residence (Home). Indian Streams Research Journal, 2(11), 1-4. Mohit M. A., Ibrahim, M. & Rashid, Y. R. (2010). Assessment of residential satisfaction in newly designed public low-cost housing in Kuala Lumpur, Malaysia. Habitat Int., 34(1), 18-27. Link Moos, R. & Lee, E. (1979). Comparing residence hall and independent living settings. Research in Higher Education, 1(3). 2007-221. Link Morgan, M. R. (2015). Thermostat behaviors and energy consumption habits in Residence Halls at Texas State University. Doctoral dissertation, Texas State University. Link Mullen, B. & Felleman, V. (1990). Tripling in the dorms: A meta-analytic integration. Basic and Applied Social Psychology, 11(1), 33-43. Link ONU - Nações Unidas (1992). Agenda 21. Department of Economic and Social Affairs, Division of Sustainable Development. Link O’Connell, M., Rosenheck, R., Kasprow, W. & Frisman, L. (2006). An examination of fulfilled housing preferences and quality of life among homeless persons with mental illness and/or substance use disorders. Journal of Behavioral Health Services & Research, 33(3), 354-365. Link Ogan C. L., Ozakca, M. & Groshek, J. (2008). Embedding the internet in the lives of college students online and offline behavior. Soc. Sci. Comput. Rev., 26(2), 170-177. Link Oppewal, H., Poria, Y., Ravenscroft, N. & Speller, G. (2005). Student preferences for university accommodation: An application of the stated preference approach. In: Mira, R.G. (ed.) Housing, space and quality of life. Burlington, USA: Ashgate Publishing. Parece, T., Younos, T., Grossman, L. S. & Geller, E. S. (2013). A study of environmentally relevant behavior in university residence halls. International Journal of Sustainability in Higher Education, 14(4), 466-481. Link Pascarella, E. T. & Terenzini, P. T. (2005). How college affects students: a third decade of research. San Francisco: Jossey-Bass. Pike, G. R. (2009). The differential effects of on and off-campus living arrangements on students' openness to diversity. NASPA Journal, 46(4), 629-645. Link Riker, H. C. & Decoster, D. A. (2008). The educational role in college student housing. Journal of College and University Housing, 35(2), 80-85. Link Rocconi, L. M. (2011). The impact of learning communities on first year students’ growth and development in college. Research in Higher Education, 52(2), 178-193. Link Salleh AG (2008). Neighborhood factors in private low-cost housing in Malaysia. Habitat. Int., 32(4), 485-493. Link Santos, G. F. M. (2012). Residentes universitários da UFS: Dinâmicas identitárias, estereótipos e ambivalência. (Mestrado), Universidade Federal de Sergipe, São Cristóvão. Link Shah, C. (2010). ContextMiner. Link Silva, L. W. S., Nunes, E. C. D. A., Teixeira, E. R., Martins, L. A., Silva, E. M. S. & Nóbrega, S. S. (2013). A arte do viver no contexto das repúblicas universitárias. Revista de Enfermagem UFPE, 7(2), 518-526. Link Thakkar, D. (2012). Diary of a fresher-2. Dhirubhai Ambani Institute of Information and Communication, Gundhinagar. Link Wang, D. & Li, S. (2006). Socio-economic differentials and stated housing preferences in Guangzhou, China. Habitat International, 30(2), 305-326. Link hite, C., Kolble, R., Carlson, R., Lipson, N., Dolan, M., Ali, Y. & Cline, M. (2003). The effect of hand hygiene on illness rate among students in university residence halls. American Journal of Infection Control, 31(6), 364-370. Link Yeung, R. (2009). A quasi-experimental approach to estimating the impact of Collegiate Housing. Annual Appam Research Conference, 31. PROCESSO EDITORIAL Submissão: 11 FEV 2017; Avaliação: FEV-MAR; Revisões: AGO-OUT. Aceite: 20 NOV 2017